Handbook of Computational Social Science for Policy 2023
DOI: 10.1007/978-3-031-16624-2_21
|View full text |Cite
|
Sign up to set email alerts
|

Social Interactions, Resilience, and Access to Economic Opportunity: A Research Agenda for the Field of Computational Social Science

Abstract: We argue that the increasing availability of digital trace data presents substantial opportunities for researchers and policy makers to better understand the importance of social networks and social interactions in fostering economic opportunity and resilience. We review recent research efforts that have studied these questions using data from a wide range of sources, including online social networking platform such as Facebook, call detail record data, and network data from payment systems. We also describe o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Integration courses in Germany include German language instruction and modules on the country's history, laws, and cultural norms. Studies identified integration courses as successful after assessing that Syrians in locations with more completed integration courses are, on average, better integrated (Kuchler & Stroebel, 2023). Despite some criticism, i.e., lack of adequate assessment of the educational competencies and needs of refugees, Germany is a country that provides adequate opportunities for refugees to integrate into the country's regular school system by meeting the German language requirement.…”
Section: G Ermany: Well-reg Ul Ated Prog R Ams Efficient Outcome Smentioning
confidence: 99%
“…Integration courses in Germany include German language instruction and modules on the country's history, laws, and cultural norms. Studies identified integration courses as successful after assessing that Syrians in locations with more completed integration courses are, on average, better integrated (Kuchler & Stroebel, 2023). Despite some criticism, i.e., lack of adequate assessment of the educational competencies and needs of refugees, Germany is a country that provides adequate opportunities for refugees to integrate into the country's regular school system by meeting the German language requirement.…”
Section: G Ermany: Well-reg Ul Ated Prog R Ams Efficient Outcome Smentioning
confidence: 99%